Exlosures used to section of specific areas at Camp Finney Wapusk National Park - Bazely, Dawn (1981)
Two of the exclosures used to collect data and section off specific areas at Camp Finney, Wapusk National Park. Some small bodies of water are also seen in the background of the along with the equipment used to set up the exclosures